Association between number of live births and markers of subclinical atherosclerosis: The Dallas Heart Study. (29th August 2020) - Sanghavi, Monika; Kulinski, Jacquelyn; Ayers, Colby R; Nelson, David; Stewart, Robert; Parikh, Nisha; de Lemos, James A; Khera, Amit
Abstract: Aims: Higher parity has been associated with increased maternal risk of cardiovascular disease, but the mechanism is not well delineated. Whether the number of live births is associated with coronary and aortic subclinical atherosclerosis has not been fully evaluated. Methods and results: Women from the Dallas Heart Study, a multiethnic population-based cohort of subjects aged 30–65 years, were included if they had data on self-reported live births and coronary artery calcium (CAC) measured by computed tomography or aortic wall thickness (AWT) by MRI. Coronary artery calcium was positive if >10 Agatston units, and aortic wall thickness if greater than the 75 th percentile reference point for age and gender. Among the 1644 women included in the study, the mean age was 45 years and 55% were Black. Sequential multivariable models were done adjusting for age, race, traditional cardiovascular risk factors, body mass index, income, education, hormone replacement therapy, oral contraceptives, and physical activity. Using women with 2–3 live births as the reference, those with four or more live births had an increased prevalence of elevated coronary artery calcium (odds ratio (OR) 2.2, 95% confidence interval (CI) 1.28–3.65) and aortic wall thickness (OR 1.6, 95% CI 1.04–2.41). Women with 0–1 live births also had increased coronary artery calcium (OR 1.9, 95% CI 1.16–3.03) and aortic wall thickness (OR 1.5, 95% CI 1.05–2.09) after multivariable adjustment. Conclusion: The number of live births is associated with subclinical coronary and aortic atherosclerosis, with an apparent U-shaped relationship. Further studies are needed to confirm this association and explore the biological underpinnings of these findings.